Enhanced Efficiency of the Sieve Tray in a Desulfurization Spray Scrubber - Qirong, Wu; Mengli, Wu; Yungui, Du; Cunfang, Lu; Jianhong, Chen (Frontiers in Energy Research, 2022)
Wet flue gas desulfurization (WFGD) system is widely used in coal-fired power plants worldwide, to improving the efficiency is very important for economical running. In this study, SO2 removal by the spray scrubber with adding a new sieve tray was studied and compared to that by the traditional spray scrubber without sieve tray (the WFGD system). The effects of gas flow rate, liquid flow rate, inlet SO2 concentration, and pH value on both types of scrubbers were evaluated. Pore diameter and porosity of the sieve tray in the sieve-tray spray scrubber were determined, and its enhanced efficiency under different experimental conditions was calculated. The results showed that the enhanced efficiency increased with increasing liquid flow rate, gas flow rate under the same liquid/gas ratio (L/G), and pH value. Compared to the spray scrubber without sieve tray, the sieve-tray spray scrubber had a significantly higher efficiency. The enhanced efficiencies were mostly between 20% and 60% at the experimental range.